2011
DOI: 10.1007/s12307-011-0073-8
|View full text |Cite
|
Sign up to set email alerts
|

The PCa Tumor Microenvironment

Abstract: The tumor microenvironment (TME) is a very complex niche that consists of multiple cell types, supportive matrix and soluble factors. Cells in the TME consist of both host cells that are present at tumor site at the onset of tumor growth and cells that are recruited in either response to tumor-or host-derived factors. PCa (PCa) thrives on crosstalk between tumor cells and the TME. Crosstalk results in an orchestrated evolution of both the tumor and microenvironment as the tumor progresses. The TME reacts to PC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 154 publications
1
19
0
Order By: Relevance
“…In prostate cancer, the activation and secretion to the extracellular environment of soluble factors that mediate the cross-talk between tumor cells and tumor stroma, such as interleukins and growth factors, has been reported to play a role in tumor progression (13,14,(38)(39)(40). Our analysis confirm a previously result that demonstrated that Brachyury increases the expression and secretion of TGFb1 in a prostate cell line (13).…”
Section: Discussionsupporting
confidence: 89%
“…In prostate cancer, the activation and secretion to the extracellular environment of soluble factors that mediate the cross-talk between tumor cells and tumor stroma, such as interleukins and growth factors, has been reported to play a role in tumor progression (13,14,(38)(39)(40). Our analysis confirm a previously result that demonstrated that Brachyury increases the expression and secretion of TGFb1 in a prostate cell line (13).…”
Section: Discussionsupporting
confidence: 89%
“…Taken together, our results indicate that pretreatment of mice with dietary phytochemicals established a microenvironment in which tumor initiation and subsequent development and progression was diminished. Studies have suggested that the tumor microenvironment play an essential role in tumor progression . An important observation of the current study is that the microenvironment is important not only for tumor progression but also for tumor initiation, which is the essence of chemoprevention.…”
Section: Discussionmentioning
confidence: 74%
“…In general, the expression and activation of MMPs correlate with advanced tumor stage, increased tumor angiogenesis, invasion, metastasis, and poor prognosis. MMPs, especially MMP-1, MMP-2, MMP-7, MMP-9, and MT1-MMP, are expressed in human PCa tissues and are involved in the establishment and growth of metastatic PCa in bone (64). Therefore, MMPs constitute an attractive target for intervention in PCa bone metastasis.…”
Section: Agents Targeting the Bone Matrixmentioning
confidence: 99%